Cinnamomum verum extract as a potential therapeutic for atopic dermatitis through reducing lipid peroxidation and oxidative stress - Kim, Min Jung; Jang, Mi Jin; Yang, Ju-Hye; You, Young Zoo; Yang, Ye Jin; Heo, Ji Woong; Choi, Han Nim; Jeon, Ryounghoon; An, Sang-Hyun; Park, Kwang Il (Frontiers in Pharmacology, 2026)
BackgroundOxidative stress and lipid peroxidation play crucial roles in the pathogenesis of atopic dermatitis (AD). Among the by-products of lipid peroxidation, 4-hydroxynonenal (4-HNE) is known to exacerbate inflammatory responses.MethodsThis study investigated the potential of Cinnamomum verum J. Presl. [Lauraceae] extract (CVE) in mitigating oxidative stress and suppressing 4-HNE–mediated inflammatory pathways in an AD model. The antioxidant properties of CVE were evaluated through lipid peroxidation assays, reactive oxygen species (ROS) measurement, and cytokine profiling.ResultsCVE treatment significantly reduced 4-HNE levels, decreased pro-inflammatory cytokine expression, and restored antioxidant enzyme activity.ConclusionThese findings suggest that CVE may serve as a natural therapeutic agent for managing oxidative stress and inflammation in AD.